Records of Gonioplectrus hispanus (cuvier, 1828) (actinopterygii: epinephelidae) in Bahia state (northeastern of Brazil), western Atlantic Ocean - Sampaio, Cláudio L. S.; Lopes, Paulo Roberto D.; de -Silva, Jailza T.; Malafaia, Priscilla; Olavo, George (Arquivos de Ciências do Mar, 2018)
The presence of Gonioplectrus hispanus (Cuvier, 1828) (Actinopterygii, Epinephelidae) is recorded to Bahia state, northeastern coast of Brazil (Western Atlantic Ocean) based in 8 specimens measuring between 247 and 2920 mm of total length (between 207 and 241 mm of standard length). Diet, reproduction, morphometric (with corporal proportions) and meristic data are presented and compared with the literature about this species.